The Impact of E-Learning on Students’ Academic Achievement in English - Saputra, Ari; Hidayani, Hidayani (Lembaga Yasin AlSys, 2021)
This research aimed at knowing the impact of e-learning on students’ achievement. The method used in this study was a quantitative research with one group pre-test and post-test design. The number of students were 43 students and the number of sample was the whole sum of the population (population sampling). The data collection was done by administring pre-test and post-test to the sample of the study. F test used to analyze the impact of e-learning method on students’ achievement in english. The statistical analysis has described that the mean score of pre-test and post-test was 71.63 and the mean score of post-test was 80.23. by using F test at the level of significance 5% the present researcher got F> F table. It’s mean that e-learning method was impact on students’ achievement in english. Furtheremore, by using Tukeys HSD continued test, the researcher got average score from pre-test and post-test were increased. It was suggestted to conduct research using e-learning method with other media such as zoom app or microsoft team.